Modern educator`s information culture as readiness formation factor to application of innovative technologies - Marta I. Diri (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In this article the professional competence of modern educators is considered, which presupposes the possession of an information culture due to the increased requirements imposed by the modernization of the educational system. The analysis of social, pedagogical, psychological, methodical literature has been made, as a result the concept «educator`s information culture» is concretized, the essence and structure of the given concept have been defined. As a result of the theoretical analysis, it was revealed that educators` information culture is one of the conditions of their readiness to become professional in the use of modern innovative educational technologies. This is due to the fact that the opportunities that have arisen with the arrival of technology in the educational process allow a modern educator to make the classes more interesting, not only with the help of finished multimedia products, but also through their own creative innovations. The systematic use of innovative technologies in combination with traditional methods significantly increases educational process effectiveness. It turned out that talking about the concept of educator`s information culture, it is necessary to distinguish three of its different meanings:ability to work with information and software; to use information and communication technologies (ICT) to achieve professionally significant goals;creative approach in the application of computer technologies at various events; non-stop self-improvement;educators` knowledge in the field of didactics and the theory of education.